Salt Reduction Initiatives around the World – A Systematic Review of Progress towards the Global Target - Trieu, Kathy; Neal, Bruce; Hawkes, Corinna; Dunford, Elizabeth; Campbell, Norm; Rodriguez-Fernandez, Rodrigo; Legetic, Branka; McLaren, Lindsay; Barberio, Amanda; Webster, Jacqui (PLOS ONE, 2015)
Objective To quantify progress with the initiation of salt reduction strategies around the world in the context of the global target to reduce population salt intake by 30% by 2025. Methods A systematic review of the published and grey literature was supplemented by questionnaires sent to country program leaders. Core characteristics of strategies were extracted and categorised according to a pre-defined framework. Results A total of 75 countries now have a national salt reduction strategy, more than double the number reported in a similar review done in 2010. The majority of programs are multifaceted and include industry engagement to reformulate products (n = 61), establishment of sodium content targets for foods (39), consumer education (71), front-of-pack labelling schemes (31), taxation on high-salt foods (3) and interventions in public institutions (54). Legislative action related to salt reduction such as mandatory targets, front of pack labelling, food procurement policies and taxation have been implemented in 33 countries. 12 countries have reported reductions in population salt intake, 19 reduced salt content in foods and 6 improvements in consumer knowledge, attitudes or behaviours relating to salt. Conclusion The large and increasing number of countries with salt reduction strategies in place is encouraging although activity remains limited in low- and middle-income regions. The absence of a consistent approach to implementation highlights uncertainty about the elements most important to success. Rigorous evaluation of ongoing programs and initiation of salt reduction programs, particularly in low- and middle- income countries, will be vital to achieving the targeted 30% reduction in salt intake.